Hyperfractionated Radiotherapy with Concurrent Cisplatin/5-Fluorouracil for Locoregional Advanced Head and Neck Cancer: Analysis of 105 Consecutive Patients. (22nd April 2012) - Zaboli, David; Tan, Marietta; Gogineni, Hrishikesh; Lake, Spencer; Fan, Katherine; Zahurak, Marianna L.; Messing, Barbara; Ulmer, Karen; Zinreich, Eva S.; Levine, Marshall A.; Tang, Mei; Pai, Sara I.; et al.
Abstract : Objective . We reviewed a cohort of patients with previously untreated locoregional advanced head and neck squamous cell carcinoma (HNSCC) who received a uniform chemoradiotherapy regimen. Methods . Retrospective review was performed of 105 patients with stage III or IV HNSCC treated at Greater Baltimore Medical Center from 2000 to 2007. Radiation included 125 cGy twice daily for a total 70 Gy to the primary site. Chemotherapy consisted of cisplatin (12 mg/m 2 /h) daily for five days and 5-fluorouracil (600 mg/m 2 /20 h) daily for five days, given with weeks one and six of radiation. All but seven patients with N2 or greater disease received planned neck dissection after chemoradiotherapy. Primary outcomes were overall survival (OS), locoregional control (LRC), and disease-free survival (DFS). Results . Median followup of surviving patients was 57.6 months. Five-year OS was 60%, LRC was 68%, and DFS was 56%. Predictors of increased mortality included age ≥55, female gender, hypopharyngeal primary, and T3/T4 stage. Twelve patients developed locoregional recurrences, and 16 patients developed distant metastases. Eighteen second primary malignancies were diagnosed in 17 patients. Conclusions . The CRT regimen resulted in favorable outcomes. However, locoregional and distant recurrences cause significant mortality and highlight the need for more effective therapies to prevent and manage these events.